Achieving correlated differential privacy of big data publication. Issue 82 (May 2019) - Lv, Denglong; Zhu, Shibing
Abstract: For protecting privacy of correlated data in big data, k-CRDP and r-CBDP models are proposed. Firstly r-CBDP uses MIC and machine learning to determine dependencies between data, accurately calculates correlated sensitivity, then divides big data into independent blocks, and implements k-CRDP for blocks to achieve big data correlated differential privacy.